Reliability and validity of the East Asian children's version of mini-MACS in children with cerebral palsy - Hou, Xiaohui; Qiu, Huiying; Liu, Liru; Li, Yinhua; He, Lu; Li, Jinling; Tang, Hongmei; Xu, Kaishou (Frontiers in Rehabilitation Sciences, 2022)
Background: Mini-Manual Ability Classification System (Mini-MACS) was developed for children with cerebral palsy aged 1 to 4 years, but its validity and reliability in different cultures were unavailable yet. This study was to determine the reliability and validity of Mini-MACS in children with cerebral palsy and investigate the correlation between Mini-MACS and Gross Motor Function Classification System. Methods: One hundred and four children with cerebral palsy aged 12 to 48 months were classiﬁed by one of their parents, an occupational therapist and a physical therapist with Mini-MACS. The results were analyzed for inter-rater reliability by using intraclass correlation coefficient (ICC). Nine-hole Peg Test was used for the criterion-related validity analysis, and parents retested their children after two weeks to evaluate test-retest reliability. Gross Motor Function Classification System levels were also collected to investigate the correlation with Mini-MACS. Results: Good inter-rater reliability among the occupational therapist, physical therapist and parents was found [ICC=0.984 (95%CI 0.976-0.989), 0.973 (95%CI 0.960-0.982), 0.966 (95%CI 0.950-0.977) respectively; p<0.01]. The test-retest reliability in parents was almost prefect [ICC=0.985 (95%CI 0.977-0.990), p<0.01]. Mini-MACS had consistency with Nine-hole Peg Test (r=0.582, 0.581, 0.566 respectively; p<0.01). A correlation was found between Gross Motor Function Classification System and Mini-MACS (r=0.626, 0.596, 0.598 respectively; p<0.01). Conclusions: The Mini-MACS demonstrates evidence that it is a valid and reliable tool to classify manual ability in East Asian children with cerebral palsy and is also positively related to the Gross Motor Function Classification System.